ANALISIS FAKTOR PENDUKUNG PERUBAHAN PERILAKU WARGA BINAAN PEMASYARAKATAN RUMAH TAHANAN NEGARA KLAS IIB RANGKASBITUNG - Ade Hadiono Ade Hadiono (LPPM STIA Banten, 2016)
Apart from being a place to accommodate convicts, the State Detention Center (Rutan) is also a place for coaching by officers in the hope that after the detainees have undergone the punishment process, they can return to society as normal people and be accepted by society without showing the person concerned as a former convict. From the facts on the ground, it turns out that there are still inmates who have finished serving their sentences, repeated their crimes, and were processed and returned as residents of state prisons. This shows that the assimilation program carried out by prison officers has not been completely successful in changing the behavior of inmates. This research is intended to identify and analyze the factors supporting changes in the behavior of prisoners in the Rangkasbitung Class IIB State Detention Center. The test results are based on the test results using Crosstabs (cross table) and looking at the results of the Pearson Chi-Square test compared to the chi-square value with an alpha of % = 3.841. Based on the results of these tests, several factors that support changes in the behavior of the prisoners are: 1) The treatment of officers towards prisoners; 2) Officers differentiate the social status of WBP; 3) Training guided by prison officers; 4) Self-motivation to be free; 5) Religious activities; 6) Frequently getting advice from religious scholars; and 7) Interaction with fellow WBP.